Effect of COVID-19 isolation measures on physical activity of children and their parents, and role of the family environment: a cross-sectional study - Amagliani, G.; Baldelli, G.; Italiano, P.; Frisina, P.; Schiavano, G. F.; Brandi, G.; De Santi, M. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The rigorous isolation measures due to the COVID-19 pandemic seriously impacted children’s lifestyles. A descriptive cross-sectional study was carried out to collect and analyze information about physical activity habits of children and their parents during the social distancing period resulting from the COVID-19 pandemic.Methods. An online questionnaire was administered to 363 families (507 children aged 5-13) recruited by convenience sampling, asking for physical activity type and frequency before, during, and after the lockdown period (9th March - May 3rd 2020), education, outdoor spaces, and children’s weight gain perception. Results. Results show a remarkable decrease in children’s physical activity during lockdown (88.9 vs 39.8% active children) associated with older age and low availability of outdoor spaces (p